Blended police firearms training improves performance in shoot/don't shoot scenarios: a systematic replication with police cadets - Olma, Joshua; Sutter, Christine; Sülzenbrück, Sandra (Frontiers in Psychology, 2024)
Senior police officers' tactical gaze control and visual attention improve with an individual videobased police firearms training. To validate the efficacy of said intervention training, a previous experiment was systematically replicated with a sample of N = 52 second-year police cadets. Participants were randomly assigned to the intervention training that focused on situational awareness, tactical gaze control, and visual attention, or an active control training that addressed traditional marksmanship skills. In a pre-and post-test, they had to engage in dynamic shoot/don't shoot video scenarios in an indoor firing range. Overall, the previous findings were replicated: Baseline levels of performance were elevated, yet the intervention group significantly improved their response time and time until the first hit. False positive decision-making cannot be reported at all; false negatives were marginal in the pre-test and eliminated after training. Further, the outcomes of the previous sample of senior officers and the present sample of cadets are compared and lead to the conclusion that the presented approach is a valuable extension of current training standards for both senior police officers and police cadets.